Distributed event‐triggered cooperative H∞ load frequency control for interconnected networked power systems - Zhihong Huo (Wiley, 2021)
Abstract Interconnected communication time‐varying delays between subsystems for large scale distributed networked power systems (DNPSs) are studied in this work. Distributed event‐triggered mechanisms‐based interconnected DNPSs and their cooperative H∞ stability control strategy are proposed for load frequency control in multi‐area interconnected power systems. Considering the distributed interconnected DNPSs, the subsystems have their own state time‐delay, and there are time‐varying delays and package dropout in subsystems interconnection; in order to reduce the amount of transmitted signals and improve the efficiency of the network communication resource, a distributed event‐triggered mechanisms‐based system model and a novel design method for networked cooperative H∞ control strategy are proposed. Based on the Lyapunov stability analysis method, a suitable Lyapunov Krasovskii function is constructed, and the distributed controller design scheme is derived based on the feasible solution of linear matrix inequality (LMI). The sufficient conditions for the system asymptotical stability is given. Finally, a four‐area networked interconnected hybrid power system is considered and the system performance under networked load fluctuations is analysed; the simulation results show that the proposed scheme is feasible and effective.